Prevalent, persistent, and impairing: Longitudinal course and impact of apathy in Alzheimer's disease. Issue 1 (5th February 2022) - Grossman, Hillel T.; Sano, Mary; Aloysi, Amy; Elder, Gregory A.; Neugroschl, Judith; Schimming, Corbett; Soleimani, Laili; Zhu, Carolyn W.
Abstract: Introduction: Understanding of the natural history of apathy and its impact on patient function is limited. This study examines, in a large, national sample of Alzheimer's disease (AD) patients with long follow‐ups: (1) prevalence, incidence, and persistence of apathy, and (2) impact of apathy on function across dementia severity. Methods: A longitudinal study of 9823 well‐characterized AD patients in the National Alzheimer's Coordinating Center Uniform Data Set. Results: Apathy was highly prevalent across disease severity with cumulative prevalence of 48%, 74%, and 82% in Clinical Dementia Rating (CDR) 0.5, 1.0, and 2.0, respectively. Persistence of apathy from clinician judgment varied from visit to visit at earlier disease stages but remained high at moderate dementia. Independent of cognition, persistent apathy was strongly associated with accelerated rate of functional decline. Discussion: Findings point to important targets for the treatment and management of apathy, include functional outcomes, and study designs that account for variable persistence of the apathy syndrome.